Mitochondrial Dysfunction Contributes to Aging-Related Atrial Fibrillation. (29th April 2021) - Liu, Chuanbin; Bai, Jing; Dan, Qing; Yang, Xue; Lin, Kun; Fu, Zihao; Lu, Xu; Xie, Xiaoye; Liu, Jianwei; Fan, Li; Li, Yang
Abstract : The incidence of atrial fibrillation (AF) increases with age, and telomere length gradually shortens with age. However, whether telomere length is related to AF is still inconclusive, and the exact mechanism by which aging causes the increased incidence of AF is still unclear. We hypothesize that telomere length is correlated with aging-related AF and that mitochondrial dysfunction plays a role in this. This research recruited 96 elderly male patients with AF who were admitted to the Second Medical Center of Chinese PLA General Hospital from April to October 2018. After matching by age and gender, 96 non-AF elderly male patients who were admitted to the hospital for physical examination during the same period were selected as controls. Anthropometric, clinical, and laboratory analyses were performed on all subjects. The mitochondrial membrane potential (MMP) of peripheral blood leukocytes was detected as the indicator of mitochondrial function. Compared with the control group, the leukocyte telomere length (LTL) was significantly shorter (P < 0.001 ), and the level of PGC-1 α in serum was significantly lower in AF patients. Additionally, in subjects without any other diseases, the AF patients had lower MMP when compared with the control. Multivariate logistic regression confirmed that LTL (OR 0.365; 95% CI 0.235-0.568; P < 0.001 ) and serum PGC-1 α (OR 0.993; 95% CI 0.988-0.997; P = 0.002 ) were inversely associated with the presence of AF. In addition, ROC analysis indicated the potential diagnostic value of LTL and serum PGC-1 α with AUC values of 0.734 and 0.633, respectively. This research concludes that LTL and serum PGC-1 α are inversely correlated with the occurrence of aging-related AF and that mitochondrial dysfunction plays a role in this.